Izazovi oblikovanja programske osnove za savremenu univerzitetsku biblioteku - Kodrić Zaimović, Lejla (Knjižnica, 2019)
The goal of this article is to problematize the approach to design a draft programme for a modern university library in order to support the integration of a traditional, decentralized university. The starting points are the university's development plans and the efforts to determine the optimal basis for the functional and coordinated library activities in the new university library building. The article focuses on basic principles of organization and management of the university library and information system and the challenges of developing new services that can attract users and position the library as one of the fundamental infrastructure pillars of the university in the 21st century. In order to prepare plans for the new library building, the first preliminary investigation about users' habits, needs and expectations was carried out. In this article, the results of the online questionnaire conducted among members of the University (teachers, researchers, students and other staff) are presented. The results will be used to plan future steps in the process of preparations for building and moving the library to the new premises.
Keywords: 21.st.; arhitektura; načrtovanje; Sarajevo; univerzitetne knjižnice; visokošolske knjižnice